Didattica generale: dai temi emergenti allo statuto epistemologico - Giuliano Franceschini (Firenze University Press, 2018)
Contemporary teaching is characterized by some emerging themes: skills, metacognition, inclusion. These themes are closely linked and involve the organization of educational learning environments favorable to the development of cognitive and social self-regulation. General teaching has the task of training teachers and managers in this direction. For this reason it presents itself today as a frontier discipline that interacts with epistemology, pedagogy and psychology to link the educational and istructive aspects, studying the relationships between affective and cognitive aspects in curriculum design.